2017
DOI: 10.1055/s-0043-121696
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation eines proaktiv angebotenen Gesundheitsprogramms für Versicherte mit anhaltenden Rückenschmerzen – Ein-Jahres-Follow-up einer randomisierten, kontrollierten Studie

Abstract: To facilitate access to evidence-based care for persisting back pain, a private medical insurance developed a health programme and offered it proactively to their members. The aim of this study was to evaluate the feasibility and efficacy of this procedure. The design of the study was a Zelen randomized controlled trial. Adult insured persons with persistent back pain were randomized to the control (CG) or intervention group (IG) prior to giving consent. The IG was invited to participate in the health programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Since 2014, Generali Deutschland has been operating a German-wide primary care intervention using a biopsychosocial approach that is offered proactively to clients suffering from CLBP. The intervention consists of a 12-month programme of spine muscle stabilising training, behavioural change telephone coaching, and patient education [42,43]. Whereas training was conducted exclusively on-site at specific treatment centres before the pandemic, it had to be performed primarily with the Kaia mobile app [44][45][46] during pandemic lockdowns, when access to local training facilities was tightly restricted or closed [47].…”
Section: Settingmentioning
confidence: 99%
“…Since 2014, Generali Deutschland has been operating a German-wide primary care intervention using a biopsychosocial approach that is offered proactively to clients suffering from CLBP. The intervention consists of a 12-month programme of spine muscle stabilising training, behavioural change telephone coaching, and patient education [42,43]. Whereas training was conducted exclusively on-site at specific treatment centres before the pandemic, it had to be performed primarily with the Kaia mobile app [44][45][46] during pandemic lockdowns, when access to local training facilities was tightly restricted or closed [47].…”
Section: Settingmentioning
confidence: 99%
“…The intervention was accompanied by a controlled trial in Zelen's -Design, registered at the German Clinical Trials Register under DRKS00015463. Results showed medical effectiveness in the 12-month follow-up [31,32]. To nd out whether the intervention is also cost-effective, inpatient as well as outpatient costs, the development of sick days due to BP and the overall health status of the participants enrolled in the aforementioned study were collected and analysed in detail.…”
Section: This Paper Addresses the Gap And Ful Ls The Consolidated Health Economic Evaluation Reportingmentioning
confidence: 99%
“…The present economic evaluation reuses data from a two-arm randomised controlled evaluation study in parallel-group Zelen's design for which recruitment took place between April and October 2015 [31,32] and amends it with administrative direct health costs data. Searches in the database of the PHI identi ed adults with administrative indications of CLBP.…”
Section: Target Population and Subgroupsmentioning
confidence: 99%
“…Besides feasibility and acceptance, efficacy, benefit and cost analyses were additional objectives of this study. First follow-up data collected shortly after the end of the program gave reason to suppose that this approach had beneficial effects [17]. In this study, we analyze the long-term effects on outcomes as reported by patients and discuss ways to improve the effectiveness of this approach to treatment of BP.…”
Section: Introductionmentioning
confidence: 99%